A Survey on Secure Binary Image Steganography Based on Minimizing the Distortion on the Texture - Mol M, Honey; Reji P.I, Prof.Mrs. (IJRDO -Journal of Computer Science Engineering, 2016)
Many of the binary image steganographic techniques only consider the flipping distortion according to the HVS( Human Visual System), which will be not secure . Here, a binary image steganographic scheme is to minimize the embedding distortion on the texture . To extract the complement, rotation, and mirroring-invariant local texture patterns (crmiLTPs)from the binary image . The weighted sum of crmiLTP changes when flipping one pixel is then used to measure the flipping distortion corresponding to that pixel. By testing on simple binary images and the new image data set, the results shows that the proposed scheme can well describe the distortions on both visual quality and statistics.This scheme generates the cover vector by dividing the scrambled image into super pixels. Experimental results show that the proposed scheme can achieve statistical security without degrading the image quality or the embedding capacity. In this paper describes survey on image steganographic techniques and steganographic techniques used with different cryptographic algorithms, to provide extra layer of Security.